Facilitating 7th Grade Students’ Food Literacy through Science Activities: A Qualitative Study - Sevill Kurt; Nagihan Yıldırım; Bahar Aksu Sandıkçı (Universitas Pendidikan Indonesia, 2022)
This study aims to discuss the development of secondary 7th-grade students' opinions on food literacy within the scope of a series of teaching activities. Through a case study, the study sample comprised 14 grade seven students, in a state secondary school in the province of Rize in Türkiye. The data was collected through semi-structured interviews before and after the implementation and the reflective diaries written by the students during the implementation. The collected data were analyzed using content analysis and descriptive analysis techniques. As a result, it was found out that the students’ knowledge structures and understandings of food literacy changed positively in many aspects during the implementation. Besides, it was seen that the implementation helped the students improve their knowledge and behaviors of food literacy. In the study, it was suggested to organize similar intervention studies for different age groups and to conduct studies in which parents are participants